Official Report upon the Mines, Metallurgy and Mining Laws, &c., &c. of the Argentine Republic - Hoskold, Henry Davis (1904)
Fil: Hoskold, H.D. Ministerio de Agricultura. Dirección de Minas y Geología; Argentina.